PEMANFAATAN FINANCIAL TECHNOLOGY SEBAGAI SARANA KEGIATAN BERTRANSAKSI: SEBUAH KAJIAN PADA MINAT KONSUMEN TERHADAP ATRIBUT PRODUK SHOPEEPAY : PEMANFAATAN FINANCIAL TECHNOLOGY SEBAGAI SARANA KEGIATAN BERTRANSAKSI: SEBUAH KAJIAN PADA MINAT KONSUMEN TERHADAP ATRIBUT PRODUK SHOPEEPAY - i, Muhamad Rifa’; Iriani, Nur Ida; Sasongko, Totok (Account: Jurnal Akuntansi, Keuangan dan Perbankan, 2023)
This study examines the effect of cashback promotion, service, expediency on the interest in using shopeepay through convenience as an intervening variable. This type of research is an influence test research with a quantitative approach. The population in this study were customers who used shopeepay. The sample determination method used is the purposive sampling method with a total of 100 respondents. Data was collected using questionnaires that were distributed to all respondents. The data was analyzed using path analysis with the Smart-PLS program. The results showed that cashback promotion had a positive and significant effect directly on the interest in using shoppepay, but did not have a direct effect on convenience and did not affect the interest in using shoppepay through convenience. Service has a significant positive effect directly and indirectly on the interest in using shoppepay through convenience. Expediency has a significant positive effect directly and indirectly on the interest in use through convenience